2021
DOI: 10.2147/jir.s316560
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effect of Mesencephalic Astrocyte-Derived Neurotrophic Factor on Post-Operative Delirium via Inhibiting Inflammation and Microglia Activation

Abstract: Background The increased inflammation is closely correlated with post-operative delirium (POD). Mesencephalic astrocyte-derived neurotrophic factor (MANF) shows protective effect on inflammatory diseases. However, the relationship between MANF and POD is still undefined. This study aimed to explore the potential effect of MANF on POD. Methods Pre- and post-operative levels of MANF and inflammatory cytokines were measured in serum from POD and non-POD patients by ELISA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…95 In aged rats undergone abdominal surgery, mesencephalic astrocyte-derived neurotrophic factor (MANF) was upregulated after surgery, and recombinant human MANF reversed POD-like behaviors. 96 This finding may provide new therapeutic targets for PNDs. One should be aware that the astrocyte activation is largely dependent on microglia.…”
Section: Astrocyte Activationmentioning
confidence: 93%
“…95 In aged rats undergone abdominal surgery, mesencephalic astrocyte-derived neurotrophic factor (MANF) was upregulated after surgery, and recombinant human MANF reversed POD-like behaviors. 96 This finding may provide new therapeutic targets for PNDs. One should be aware that the astrocyte activation is largely dependent on microglia.…”
Section: Astrocyte Activationmentioning
confidence: 93%
“…The finding in the brain is interesting, since the brain was not manipulated in any way, and indicates inflammatory crosstalk between the periphery and the CNS, which is a contributing factor in stroke pathogenesis as well. In patients, the same study found implications of a negative correlation between endogenous MANF protein levels and cytokine levels in the serum after knee operation, indicating that low MANF serum levels may contribute to postoperative systemic inflammation ( Liu et al, 2021 ). Another patient study found elevated Manf mRNA levels in leukocytes in inflammatory diseases such as rheumatoid arthritis and systemic lupus erythematosus ( Chen et al, 2015 ).…”
Section: Immunomodulatory Effects Of Manfmentioning
confidence: 95%
“…A recent study found significantly reduced MANF protein levels in the brain of 18- to 20-month-old mice compared to 2- to 3-month-old mice ( Han et al, 2021 ) and additional groups of 6- and 9-month-old mice ( Liu et al, 2021 ). MANF protein expression has been also shown to decrease with aging in the fruit fly, in mouse plasma, retinal choroid, white adipose tissue, skin, liver, and muscle tissues, and in human serum and retinal choroid ( Sousa-Victor et al, 2019 ; Neves et al, 2020 ; Liu et al, 2021 ). Decreased MANF expression could predispose for many age-related diseases and worsen the outcome of stroke.…”
Section: Mesencephalic Astrocyte-derived Neurotrophic Factormentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in those patients undergoing abdominal surgery, microglial activation has been detected and associated with impairments in cognitive function [ 56 ]. Meanwhile, the endogenous mesencephalic astrocyte-derived neurotrophic factor has been shown to have positive effects on POD by inhibiting surgery-induced inflammation and microglial activation [ 57 , 58 ].…”
Section: Pathological Theoriesmentioning
confidence: 99%